2015
DOI: 10.1002/jmv.24367
|View full text |Cite
|
Sign up to set email alerts
|

The possible impact of sortilin in reducing HBsAg expression in chronic hepatitis B

Abstract: Hepatitis B virus (HBV) infection is a major global health problem. Chronically infected people are at risk for progressive hepatic fibrosis and consequent cirrhosis. Hepatitis B surface antigen (HBsAg) level in serum is a complementary marker for intrahepatic HBV DNA and covalently closed circular DNA (cccDNA). Sortilin-1 (SORT1) has been reported to be involved in the post-Golgi vesicle trafficking of Apo lipoproteins degradation pathways. This study was designed to evaluate the hepatic and serum expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Our results revealed that the HBsAg titer was independently associated with HBsAg clearance that was significantly lower in subjects who cleared HBsAg during follow-up. Effects of HBV viral load have been examined in previous studies and indicated an association between HBsAg seroclearance and lower HBV DNA levels (4,5,21). Also, they showed that serum HBsAg and both serum and liver HBV DNA were more correlated in HBeAg-positive carriers.…”
Section: Discussionmentioning
confidence: 95%
“…Our results revealed that the HBsAg titer was independently associated with HBsAg clearance that was significantly lower in subjects who cleared HBsAg during follow-up. Effects of HBV viral load have been examined in previous studies and indicated an association between HBsAg seroclearance and lower HBV DNA levels (4,5,21). Also, they showed that serum HBsAg and both serum and liver HBV DNA were more correlated in HBeAg-positive carriers.…”
Section: Discussionmentioning
confidence: 95%
“…This toxin is like DNase, in structure and activity, which breaks the double‐strand DNA and induce cellular apoptosis . Colonization by colibactin‐producing B2 phylogroups at the early life of animal experiments associated with the reduction in regulatory T‐cell populations which is a susceptibility factor for the development of immune‐mediated diseases and the predisposition of cancer . The potential effect of intestinal E. coli on colorectal cancer development is extensively evaluated in animal and human models .…”
Section: E Coli Colonization and Mechanism For Development Of Hccmentioning
confidence: 92%
“…Chronic infection is characterized by the persistence of hepatitis B surface antigen (HBsAg) synthesis. Higher production of HBsAg aggregates in the endoplasmic reticulum (ER) (main organelle in the synthesis, folding and trafficking of proteins) of hepatocytes that correlate with the cellular response known as ER stress (2,3). Recent work provided information on HBsAg quantitation that improves the understanding of treatment response and natural history of CHB (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Higher production of HBsAg aggregates in the endoplasmic reticulum (ER) (main organelle in the synthesis, folding and trafficking of proteins) of hepatocytes that correlate with the cellular response known as ER stress (2,3). Recent work provided information on HBsAg quantitation that improves the understanding of treatment response and natural history of CHB (3,4). Envelope proteins of hepatitis B virus (HBV) often appear in the form of "ground-glass" hepatocyte shown in pre-S mutants or HBV genome integration in the host genome (3,5,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation